(3OQGSGJ aj GdeMGSHI GdeGdjIs - (3GdUHGf(B, (3eMeO SejQs ((3GdGScfOQjIs (3GdOGQ GdLGeYjIs, 2002)
(3GdeMGSHI cfXGe ddeYdheGJ ,GdbjGS GdeMGSHj ddCUhd GdfbOjI ,GdjGS GdLHGFj ddCUhd ZjQ GdfbOjI GdbjGS GdeMGSHj ddCUhd GdKGHI aj bjGS GdeUQhaGJ , GdbhGYO GdeMGSHjI GdJj JMce GdbjGS GdeMGSHj aj MGdI GdSLdGJ ZjQ GdcGedIs